Renal prostaglandin synthesis in the spontaneously hypertensive rat. - Dunn, M J (1976)
The precise role of the kidney in spontaneous experimental hypertension is unknown. We have analyzed the rates of renal prostaglandin synthesis by utilizing a spontaneously hypertensive rat model. The synthetic rate of prostaglandin E2, prostaglandin F2alpha, and prostaglandin A2-like products was measured in vitro with renal microsomes. In the rabbit and rat there is a steep gradient of microsomal prostaglandin synthetase from papilla to cortex with highest activities in the papilla. Comparison of the activity of prostaglandin synthetase in medullary microsomes form normotensive and hypertensive rats showed accelerated synthesis in the spontaneously hypertensive rat. These differences appeared after several months of age, were statistically significant from 3 mo of age and, on the average, represented at least a twofold increase of in vitro activity. All classes of prostaglandins were involved with increased synthesis of prostaglandin E2, prostaglandin F2alpha and prostaglandin A2-like material. These data reenforce and extend previous work showing alterations of granularity and presumably prostaglandin synthesis in renal medullary intersitital cells in various experimental hypertensions. We also measured renal tissue content of prostaglandin E and prostaglandin A-prostaglandin B by radioimmunoassay. Swift and careful handling of the tissue was necessary to avoid extensive postmortem synthesis of prostaglandins. In rapidly-frozen medullary tissue only prostaglandin E was detectable in concentrations ranging from 10 to 200 pg/mg tissue. No significant differences were found in the medullary content of prostaglandin E in the control and hypertensive rats despite the increased rates of enzymatic synthesis. We conclude that renal prostaglandin synthesis is increased in renal medullary microsomes obtained from spontaneously hypertensive rat. This apparently occurs in response to the progressive development of hypertension since young animals did not show an increase Renal tissue prostaglandin E content did not increase and therefore appears to be a poor index of enhanced prostaglandin synthesis.